A study of crystalluria: effectiveness of including hygienic-dietary recommendations in laboratory reports - Sienes Bailo Paula (De Gruyter, 2021)
To assess the effectiveness of incorporating hygienic-dietary recommendations in laboratory reports in reducing the incidence of renal colic (RC). A study was performed to compare the incidence of RC in two groups of patients who had suffered at least a crystalluria event associated with the risk of urolithiasis. Recommendations were only incorporated in the laboratory reports of one group.